IMPLEMENTASI UNDANG-UNDANG NOMOR 27 TAHUN 2007 DALAM PENGELOLAAN PULAU DAN PERAIRAN NUSAKAMBANGAN CILACAP - Wahikun (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2017)
Law number 27 of 2007 which regulates the management of coastal and small Islands for sustainable, can not be applied to the all land of Nusakambangan.Nusakambangan Island is a small island in its outermost position, which was originally a prison island. Along with the occurrence of arising land inhabited by theresidents, the western Nusakambangan island into an uninhabited island even become the capital of sub-district kampung laut, so that HP-3 not fitt to apply in accordance with the law.